Preclinical dental training: Association between difficulty in performing restorative procedures and the adoption of ergonomic posture - Neves, Tamíris da Costa [UNESP]; Viana, Lauriane Nogueira [UNESP]; Wajngarten, Danielle [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Wiley, 2019)
Objective: The aim of this study was to determine any correlations between difficulty in performing restorative procedures and the adoption of ergonomic posture by dental students in a preclinical course. Methods: The sample was composed of second-year undergraduate students enrolled in the School of Dentistry of São Paulo State University (UNESP), Araraquara (n = 56). The data were collected from weekly records in which students who had participated in training in a preclinical restorative dentistry laboratory registered the difficulty they experienced performing given proposed preclinical procedures and adopting ergonomic posture (positioning of students’ legs, thighs, spine, arms, and forearms, as well as the positioning of both the dental light and the dental mannequin's head, the distance between the operating field and the operator's eyes, and the location of the instruments used in the procedures). Answers were provided on a scale of zero to ten points (zero = no difficulty; 10 = maximum difficulty). A descriptive statistical analysis was performed. The correlation between the level of difficulty in performing the restorative procedures and in the adoption of ergonomic posture was estimated using the Pearson correlation coefficient (r), and its significance was tested using Student's t test. To evaluate the effect of time on students’ perceived difficulties in implementing ergonomic posture, the first 2 weeks of training was defined as the initial time, whilst the last 2 weeks was defined as final time (scores from these periods were averaged). After the normality assumptions were verified, Student's t test for paired samples was performed. The significance level adopted was <5%. Results: A correlation was found between the difficulty students experienced performing the preclinical procedures and their difficulties implementing ergonomic posture; the correlation was significant, though the correlation ranged from slight to moderate (P < 0.001; r = 0.38-0.63). In addition, the data also showed that the students’ perceptions of how difficult it was to implement these posture items decreased significantly over time (P < 0.001). Conclusion: The correlation between perceived difficulty in performing the preclinical restorative dentistry procedures and the application of ergonomic posture was slight to moderate, and the students’ perceived difficulties in maintaining ergonomic posture decreased over the course of the school year.
Keywords: dental students; dentistry; ergonomics; simulation training